Buyer-supplier relationships in advanced manufacturing technology acquisition and implementation in Malaysia - Abd Rahman, Azmawani (Faculty of Economics and Management, Universiti Putra Malaysia, 2008)
In an increasingly competitive environment, manufacturing firms in developing countries have continued to acquire and implement new and advanced technologies aimed at improving plant performance. In any new technology adoption, implementation remains the main issue, having been recognised by practitioners and widely reported by researchers as a major source of project failure. This is particularly true if the technology is considered to be advanced for the firm. While many factors have been blamed for causing project failure, efforts continue to be made to identify the critical success factors in technology implementation. In the implementation of advanced manufacturing technology (AMT), the relationship between technology buyers and suppliers has been widely cited as crucial to overall success. This paper explores technology buyer-supplier relationships and both implementation and performance of technology throughout the process of acquisition and implementation. Data obtained from 147 manufacturing firms in Malaysia was used to test several hypotheses, which were derived from an extensive review of literature relating to advanced manufacturing technology and buyer-supplier relationships (BSR). The data was analysed using the structured equation modelling (SEM) technique. The results indicate that although a majority of the firms reported improvements in performance since initiating the use of AMT, firms demonstrating a closer relationship with the technology suppliers are more likely to achieve higher levels of performance than those that do not. The result of this study also provides useful insights that are especially pertinent for improved understanding of buyer-supplier relationships in the procurement of capital equipment, about which research literature is currently quite sparse.